PENGARUH PADAT PENEBARAN TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN NILA GESIT (Oreochromis niloticus) The influence of stocking density into Nila Gesit (Orechromis niloticus) survival and growth. - Frizca Junelda Karlyssa; Irwanmay Irwanmay; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
The efficiency of freshwater resources utilization is need to improve in order to increase the production. The purpose of this research is to determine the stocking density of seeds that able to increase Nila growth and survive ability. This research used Nila Gesit with average length in 3,44 cm and average weight in 0,86 gram. Nila gesit was kept in aquarium sized 60 cm x 30 cm x 30 cm, fill with 32 L of water. The research design is complete random plan with 3 treatment and 3 repeatable. The treatment of stocking density are 2 seed/l, 4 seed/l, and 6 seed/l. The results during 28 days are : the highest value 2 seed/l of survival rate (78,65 %), the value of daily growth (3,12 %), and the value of absolute growth (1,07 cm). The result for highest feed conversion in found treatment 3 (6 seed/l) is 4,29. The result has shown that difference of density stock is very significantly affecting rate of daily growth and absolute growth. While degree of survival rate and feed conversion on this research hasn't affected the stocking density. Chemical factor of water quality during the research are : DO (disolved oxygen) 2,8 – 4,9 mg/l, pH 7,1 – 8,6, temperature 26,7 -28,2.Keywords : stocking density, nila gesit, survive rate, growth.